High voltage electrochemical double layer capacitors using conductive carbons as additives - Michael, M.S.; Prabaharan, S.R.S. (2004)
We describe here an interesting approach towards electrochemical capacitors (ECCs) using graphite materials (as being used as conductive additives in rechargeable lithium-ion battery cathodes) in a Li+ containing organic electrolyte. The important result is that we achieved a voltage window of > 4 V, which is rather large, compared to the standard window of 2.5 V for ordinary electric double layer capacitors (DLCs). The capacitor performance was evaluated by cyclic voltammetry (CV) and galvanostatic charge/discharge techniques. From charge-discharge studies of the symmetrical device (for instance, SFG6 carbon electrode), a specific capacitance of up to 14.5 F/g was obtained at 16 mA/cm(2) current rate and at a low current rate (3 mA/cm2), a higher value was obtained (63 F/g). The specific capacitance decreased about 25% after 1000 cycles compared to the initial discharge process. The performances of these graphites are discussed in the light of both double layer capacitance (DLC) and pseudocapacitance (battery-like behavior). The high capacitance obtained was not only derived from the current-transient capacitive behavior but is also attributed to pseudocapacitance associated with some kind of faradaic reaction, which could probably occur due to Li+ intercalation/deintercalation reactions into graphitic layers of the carbons used. The ac impedance (electrochemical impedances spectroscopy, EIS) measurements were also carried out to evaluate the capacitor parameters such as equivalent series resistance (ESR) and frequency dependent capacitance (C-freq). Cyclic voltammetry measurements were also performed to evaluate the cycling behavior of the carbon electrodes and the non-rectangular shaped voltammograms revealed the non-zero time constant [tau(RC) not equal 0] confirming that the current contains a transient as well as steady-state components. (C) 2004 Elsevier B.V. All rights reserved.